The Influence of Individual Characteristics and Work Environment on Employee Performance at PT. PLN (Persero) ULP Karang - Rida Dwi Septiana; Hepiana Patmarina (International Journal of Economics, Business and Innovation Research, 2024)
One In the context of an organization, there are various resources that play an important role in driving its activities. However, it needs to be recognized that human resources play a very significant role in achieving success. In this era of intense competition, organizations are increasingly aware that the active participation of employees, which goes beyond their formal duties, is crucial to improving the overall effectiveness of the organization's employees. Problems at PT PLN (Persero) ULP Karang include high absenteeism rates and employee performance that has not reached the target. This study seeks to assess how individual attributes as well as the work environment influence the performance of PT PLN (Persero) ULP Karang employees. This research uses quantitative methodology to analyze primary data obtained through sending questionnaires to 56 participants. Secondary data was collected from various sources including literature, books, articles, scientific journals, theses, and related online information. Data analysis used multivariate linear regression on SPSS 27. The results showed that individual quality has a good but insignificant effect on employee performance, while the work environment has a positive and significant effect on employee performance. The results showed that the performance of PT PLN (Persero) ULP Karang personnel was influenced by individual characteristics as well as the work environment. Keywords: Individual Characteristics; Work Environment; Employee Performance